Expression of apoptotic protease activating factor-1 in adenoid cystic carcinoma of the salivary glands and its clinicopathological relevance - Dožić Branko; Aničić Boban; Sinobad Vladimir; Miković Nikola; Milanović Srđan; Dožić Ivan (Vojnosanitetski Pregled, 2022)
Background/Aim. Apoptotic protease-activating factor-1 (Apaf-1) is a key molecule in the intrinsic or mitochondrial pathway of apoptosis. Some pathological conditions, such as cancer, stroke, and neurodegenerative diseases, are the result of dysregulation in the intrinsic apoptosis pathway. The aim of this study was to analyze the immuno-histochemical expression of Apaf-1 in adenoid cystic carcinoma (ACC) cells of the salivary glands and its correlation with clinicopathological parameters of patients (gender, age, localization, histological type, and overall survival). Methods. Formalin-fixed, paraffin-embedded tissues of ACC of the salivary glands from 50 male and female patients with an average age of 58 years, were used for the study. We used the technique of tissue microarray (TMA blocks). Sections from the TMA mold, 5 μm thick, were stained with the streptavidin-biotin immunohistochemical technique using primary antibodies specific for Apaf-1 (Leica Biosystems, Newcastle, UK). Stained tissue sections were analyzed by the light microscope (Olympus type BH-2). Based on the data collected, the database was created in SPSS software v. 22.0 (SPSS Inc., Chicago, ILL, USA), which was used for further statistical analysis. The statistical data analysis included methods of descriptive and analytical (inferential) statistics. Results. The results of the immunohistochemical analysis of Apaf-1 expression in the samples of patients with ACC of the salivary glands were compared with the clinicopathological parameters of these patients. The immunohistochemical expression of Apaf-1 showed no statistical significance with regard to the patients’ gender (p = 0.552), age (p = 0.106), histological tumor type (p = 0.654), and localization of ACC in the salivary glands (p = 0.486). There was no statistically significant correlation observed between the overall survival of ACC patients and Apaf-1 expression in tumor cells (p = 0.340, Log-Rank test). Conclusion. With regard to ACC, Apaf-1 expression is not in correlation with clinicopathological parameters (gender, age, localization, histological tumor type, outcome of the disease, and overall survival). Therefore, we believe Apaf-1 cannot be regarded as an independent prognostic factor for course and outcome of ACC of the salivary glands.